Women's opportunities under different constellations of family policies in western countries: Inequality tradeoffs re-examined - Walter Korpi; Tommy Ferrarini; Stefan Englund (Luxembourg Income Study (LIS), 2010)
Women's rising labor force participation since the 1960's was long seen as heralding decreasing gender inequalities. According to influential social science writings this view has now to be revised; 'women friendly' policies bringing women into the workforce are held to create major inequality tradeoffs between quantity and quality in women's jobs. Unintendedly, such policies increase employer statistical discrimination and create glass ceilings impeding women's access to influential positions and high wages. This paper re-examines theoretical and empirical bases in analysis of family policy effects on gender inequalities. Including capabilities as well as earnings in definitions of gender inequality, we improve possibilities for causal analyses by mapping institutional constellations of separate dimensions of family policies in Western countries. Reflecting conflicting political forces as well as religion, contrary to accepted assumptions of uni-dimensionality, family policies are multi-dimensional, with main distinctions favoring traditional families, mother's employment, or market reliance. Using multilevel analyses and broad sets of outcome variables, we show that methodological mistakes largely invalidate earlier causal interpretations of major tradeoffs between quantity and quality in women's labor force participation. Positive policy effects facilitate work-family reconciliation and combine women's increased labor force participation with relatively high fertility. While major negative policy effects for women with tertiary education are difficult to find, family policies clearly differ in the extent to which they improve opportunities for women without university degrees.
Keywords: 330; Familienpolitik; Weibliche Arbeitskräfte; Familie-Beruf; Bildungsniveau; Geschlechterdiskriminierung; Frauen; Wirkungsanalyse; OECD-Staaten